Fill removal in wellbore using coiled tubing - Yong, L.H.P. (2013)
Coiled Tubing (CT) services are widely applied in oil field to remove fill from wellbore. Its function is to restore the productivity of oil and gas well since fill such as sand will regularly block the production line especially at the well bottom. Predicting the behaviors of cleaning fluid and particle transports during the CT cleanout is a major challenge because there are many variables which affect the cleaning operation resulting in loss of cleaning efficiency, waste of cleaning fluid and increase in cost of well services. The objective of this study is to perform detailed analyses of both flow pattern of cleaning fluids and particle transports in wellbore during cleaning process at different cleaning operating conditions and well geometries. In order to achieve the objective, the problem is broken down into two parts; namely the well string and the well bottom/annulus. The well string, which is the coiled tubing itself, is first solved semi-analytically to obtain the exit velocity of the flow nozzle and the accompanying surface pump operating conditions. Once the exit velocity in the coil tubing is known, the value is used as an inlet velocity boundary condition for the bottomhole and the well annulus for the subsequent CFD analysis. Simulating the cleaning process along the entire well span is impractical due to limitation in computational resources. Hence, only a limited section in the bottomhole and annulus were considered, where the calculated transport properties there is sufficient to inform the likelihood of fill being circulated to the surface. The present study identified that diameter ratio of CT and annulus, properties of the cleaning fluid, design of downhole nozzle are the three most important factors influencing the cleanout. The result of this study is a linearized CT parameters design chart that allows user to plan for cleaning operation. Â© (2013) Trans Tech Publications, Switzerland.